Culture Appropriation in Popular Media: A Critical Analysis of Globalization and Identity - Nofrizon Marzal; Saniman Andi Kafri (MD Research Center, 2025)
This article discusses the phenomenon of cultural appropriation in the context of globalization, focusing on its impact on marginalized groups and the tensions that arise between appreciation and exploitation of cultural elements. Through a literature review, the article examines how cultural appropriation practices lead to commodification, distortion, and the erasure of the original cultural meaning, as well as their effects on the identity and psychological well-being of the affected groups. The study shows that globalization, while enabling cultural exchange between countries and communities, often reinforces power imbalances, where dominant cultures take cultural elements from marginalized groups without respecting their original context or values. This phenomenon not only contributes to the loss of cultural identity but also increases feelings of alienation and devaluation among the affected individuals. The article also discusses the importance of culturally responsive education and cultural humility as efforts to mitigate the negative impacts of cultural appropriation. In the social context, cultural justice should be seen as an integral part of a larger social movement, aimed at providing space for marginalized cultural narratives and promoting respect for cultural diversity. The findings of this research emphasize that a critical understanding of cultural appropriation, with an awareness of imbalances and historical contextualization, is crucial in creating a more just society that values cultural diversity.